Antropometri dan Biomotorik Atlet Bolavoli Duduk Paralympic Indonesia ditinjau dari Karakteristik Cidera dan Kualitas Kondisi Fisik - Deddy Whinata Kardiyanto; Bambang Wijanarko (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of the study was to identify and analyze the anthropometric and biomotor skills of athletes with disabilities in sitting volleyball in terms of injury characteristics and quality of physical condition. The research method used is descriptive quantitative. Data analysis used descriptive percentage analysis technique with the help of SPSS version 24.0 application. The results of this study indicated that anthropometric and biomotor in terms of injury characteristics and quality of physical condition as an important component to improve the performance of seated volleyball athletes in terms of injury characteristics and quality of physical condition. In conclusion, to improve the performance and achievement of athletes, one of them is to identify injuries and the quality of physical conditions. Keywords: Anthropometrics, Biomotor, Injury, Physical Condition, Sitting Volleyball